2006
DOI: 10.5395/jkacd.2006.31.1.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shaping ability between various hybrid instrumentation methods with ProTaper

Abstract: The purpose of this study was to compare and evaluate the shaping abilities of various hybrid instrumentation method using constant tapered file systems with ProTaper � S1 and the difference between experts and inexperienced clinicians in use of NiTi file.Three hybrid methods used in this study were composed of ProTaper � S1 and K-Flexofile � (group S), ProTaper � S1 and HeroShaper � (group H), and ProTaper � S1 and ProFile � (group P), respectively. The ProTaper � -alone method (group C) was introduced as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Particularly, at 2 ㎜ level the two ProTaper systems showed significantly lesser centering ratios than Group H. The ProFile had the better centering ability than the other groups in most of evaluated levels. This finding is consistent with other studies to evaluate the centering ratio or shaping ability of various NiTi files including ProFile 24,28) . Hong et al 24) recommended, through the comparison of various hybrid instrumentation technique, that if the apical regions are to be enlarged wider than ISO 30, it might be better to use a different system 12) .…”
Section: ⅳ Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Particularly, at 2 ㎜ level the two ProTaper systems showed significantly lesser centering ratios than Group H. The ProFile had the better centering ability than the other groups in most of evaluated levels. This finding is consistent with other studies to evaluate the centering ratio or shaping ability of various NiTi files including ProFile 24,28) . Hong et al 24) recommended, through the comparison of various hybrid instrumentation technique, that if the apical regions are to be enlarged wider than ISO 30, it might be better to use a different system 12) .…”
Section: ⅳ Discussionsupporting
confidence: 82%
“…This finding is consistent with other studies to evaluate the centering ratio or shaping ability of various NiTi files including ProFile 24,28) . Hong et al 24) recommended, through the comparison of various hybrid instrumentation technique, that if the apical regions are to be enlarged wider than ISO 30, it might be better to use a different system 12) . But this study showed that all experimental system makes similar centering ratio except Group P. Schäfer et al 16) reported that ProTaper tended to transport towards the outer aspect of the canal curvature.…”
Section: ⅳ Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, there was no statistical difference in instrument distortion that occurred only group MT, which can be interpreted due to using new files in each canal 26) and the adoption of torque control motors for the experiment 26,27) . The fact that none of the Mtwo files fractured after enlargement of canal may be due to the increasing pitch length from the tip to the shaft of these instruments 8) .…”
Section: ⅳ Discussionmentioning
confidence: 97%